PENGARUH PEMBELAJARAN, PEMBERDAYAAN FAKTOR INTERNAL DAN EKSTERNAL TERHADAP MINAT BERWIRAUSAHA MAHASISWA UNIBA SURAKARTA ANGKATAN 2014 - Wisnu Sembodo, Djumali & Burhanudin (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
This study aims to determine the learning, empowerment, internal factors andexternal factors affecting the interest in entrepreneurship students of the Faculty ofEconomics, University Islam Batik Surakarta. Students who were respondents of 100people were deployed at the Faculty of Economics. The data collected is the primarydata by means of questionnaires and measurements of variables using purposive randomsampling technique sampling. Data Analysis Methods usedwere validity test, reliabilitytest, t test, F test and the coefficient of determination (R²). External factors that areenvironmental factors, affect sikfikan the interest in entrepreneurship with a significantlevel of 0,05. The factors of learning, empowerment, internal factors, but not significantpositive effect on the interest in entrepreneurship. Value determinants of these threefactors is 0,265, meaning 26,5% of research variables able to determine the interest inentrepreneurship, while the remaining 73,5% is determined by variables outside theresearch. Otherwise good research model with significant F value is 0,000.Keywords: Effects of Education, Empowerment, Interest Factor External Internal,Entrepreneurship.